Changing Scenario of Indian Insurance Sector - Rajesham, Ch.; Rajender, K. (Indian Journal of Marketing, 2006)
Insurance Sector has not only been playing a leading role within the financial system in India but also has a significant socio-economic function, making inroads into the interiors of the economy and is being considered as one of the fast developing areas in the Indian financial sector too. It has also been facilitating economic development with an objective to build an efficient, effective and a stable insurance business in India as well as a strong base to both the needs of the real economy and socio-economic objectives of the country. It has been mobilising long-term savings through Life-Insurance to support economic growth and also facilitating economic development, insurance cover to a large segment of people, while the non-life insurance and reinsurance firms in India are main providers of risk financing for man made disasters and natural catastrophes. Thus, both life insurance and non-life insurance are found playing a significant role in avoiding or facing the risks of life and business enterprises and also aiding to certain extents for their smooth sailing. Therefore, an attempt is made in this paper to highlight the developments of insurance sector in India in a phased manner and to examine the reasons for the entry of private and foreign insurance players into indian insurance market and to present the changing scenario of insurance business in India. It is also attempted to examine the growth of the indian insurance sector during the period of pre and post liberalisation and finally to suggest the strategies and challenges need to be adopted by indian insurance sector in the light of global scenario so as to enhance its market share.